Follicle-stimulating hormone potentiates the steroidogenic activity of chorionic gonadotropin and the anti-apoptotic activity of luteinizing hormone in human granulosa-lutein cells in vitro. (15th February 2016) - Casarini, Livio; Riccetti, Laura; De Pascali, Francesco; Nicoli, Alessia; Tagliavini, Simonetta; Trenti, Tommaso; La Sala, Giovanni Battista; Simoni, Manuela
Abstract: Luteinizing hormone (LH) and choriogonadotropin (hCG) are glycoprotein hormones regulating ovarian function and pregnancy, respectively. Since these molecules act on the same receptor (LHCGR), they were traditionally assumed as equivalent in assisted reproduction techniques (ART), although differences between LH and hCG were demonstrated at molecular and physiological level. In this study, we demonstrated for the first time that co-treatment with a follicle-stimulating hormone (FSH) dose in the ART therapeutic range potentiates different LH- and hCG-dependent responses in vitro, measured in terms of cAMP, phospho-CREB, -ERK1/2 and -AKT activation, gene expression, progesterone and estradiol production in human granulosa-lutein cells (hGLC). We show that in the presence of FSH, hCG biopotency is about 5-fold increased, in the presence of FSH, in terms of cAMP activation. Accordingly, CREB phosphorylation and steroid production is increased under hCG and FSH co-treatment. LH effects, evaluated as steroidogenic cAMP/PKA pathway activation, do not change in the presence of FSH, which, however, increases LH-dependent ERK1/2 and AKT, but not CREB phosphorylation, resulting in anti-apoptotic effects. The different modulatory activity of FSH on LH and hCG action in vitro corresponds to their different physiological functions, reflecting proliferative effects exerted by LH during the follicular phase and before trophoblast development, and the high steroidogenic potential of hCG requested to sustain pregnancy from the luteal phase onwards. Highlights: FSH potentiates the different response to LH and hCG in granulosa cells, in vitro . LH treatment of granulosa cells results mainly in anti-apoptotic effects. hCG treatment of granulosa cells results mainly in steroidogenic effects.